Exploration of mathematical concepts in Batik Truntum Surakarta - Adi Nurcahyo; Naufal Ishartono; Alma Yasinta Candra Pratiwi; Mohamad Waluyo (Jurnal Infinity, 2024)
This research investigates the mathematical concepts embedded within Batik Truntum motifs, including geometry, analysis, arithmetic, and algebra. Employing a qualitative methodology with an ethnographic approach, the study addresses four critical questions: "Where should I begin the search?", "How do I locate the concepts?", "How do I identify significant findings?", and "How do I comprehend these findings?". Through addressing these questions, the researcher successfully analyzed the mathematical concepts inherent in Batik Truntum. Of the four primary mathematical concepts, only geometry was substantiated by experts, encompassing sub-concepts such as geometric transformations, line relationships, and planar geometry. Specifically, transformation geometry includes translation and reflection, while the study of line relationships involves line alignment, and planar geometry covers the topic of circles. This research aims to ensure that the millennial generation remains connected to batik as a vital part of Indonesia's cultural heritage, preventing cultural erosion amidst technological advancements through the intricate and exploratory study of mathematics.